Ex situ culture of coral species Porites lobata (Scleractinia: Poritidae) and Pocillopora damicornis (Scleractinia: Pocilloporidae), Costa Rica: first assessment and implications - Marín-Moraga, José A. (2023)
Introduction: Coral reefs worldwide decline has prompted coral restoration as a viable strategy to rewild vulnerable, foundational coral species. Stony corals are now propagated by thousands in both in-water and ex situ (land-based) coral nurseries, the latter being unexplored in Costa Rica, despite their potential benefits as a reef management tool. Objective: To analyze the viability of ex situ culturing of the Pacific reef-building corals Porites lobata and Pocillopora damicornis at Parque Marino del Pacífico (PMP), Puntarenas, Costa Rica, aquaculture facilities. Methods: From May to October 2018 a total of 180 coral fragments were kept in an aquaculture recirculated system. Survival, growth, and fragment yield in relation to culture medium (physicochemical parameters) were recorded. Results: Survival and growth rate varied between species and culture tanks. On average, surviving P. lobata fragments (68.89 %) placed in Tank 1 (T1) grew 216 %, while fragments placed in Tank 2 (T2) had a survival rate of 71.11 % and an increase of 277 % in live tissue area. P. damicornis fragments survival, basal and crown area percentage increase were: 71.11 %, 980 % and 366 % in T1, and 100 %, 976 % and 287 % in T2. Although fragments survival and growth were net positive, the yield in terms of culture was low, due to culture conditions in the tanks not meeting coral culture optimal requirements. Conclusions: Survival and growth of both species varied depending on the tank in which they were placed. Survival was similar to that found in other ex situ studies and growth was similar to those reported in the wild, however culture performance in terms of yield was low. Aquaculture systems at PMP constitute a good base for the cultivation of corals, however for the culture effort to achieve maximum yield, current systems must be optimized according to the requirements of the target coral species.